Correction: Shakir et al. Exorbitant Drug Loading of Metformin and Sitagliptin in Mucoadhesive Buccal Tablet: In Vitro and In Vivo Characterization in Healthy Volunteers. Pharmaceuticals 2022, 15, 686 - Rouheena Shakir; Sana Hanif; Ahmad Salawi; Rabia Arshad; Rai Muhammad Sarfraz; Muhammad Irfan; Syed Atif Raza; Kashif Barkat; Fahad Y. Sabei; Yosif Almoshari; Meshal Alshamrani; Muhammad Ali Syed (MDPI AG, 2024)
In the original publication, a mistake was observed in Figure 5 as published [...]